1991
DOI: 10.1016/0303-7207(91)90005-d
|View full text |Cite
|
Sign up to set email alerts
|

The stimulatory effect of albumin on luteinizing hormone-stimulated Leydig cell steroid production depends on its fatty acid content and correlates with conformational changes

Abstract: The effects of purified albumin species and albumin fragments (0.2-1% w/v) on short-term (4 h) steroid secretion by immature rat Leydig cells, in the presence of a maximally stimulating dose of luteinizing hormone (LH), were investigated. Human albumin and the peptic fragment (comprising residues 1-387) enhanced pregnenolone production in isolated rat Leydig cells, whereas chicken albumin and the tryptic fragment (comprising residues 198-585) were not active. This stimulatory effect of human albumin and the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 64 publications
1
10
0
1
Order By: Relevance
“…The discovered pH-induced changes in the N-form of albumin are not displayed in absorbance measurements (Figs. 5a, 5b) and were not detected by the methods of circular dichroism , 18 and 1H-NMR 17 jll as by use of other fluorescent probes monitoring N->B transition in serum albumin (ANS, bilirubin, warfarin, dansylaniide) 21, 22 A decrease in the HSA-NR affinity upon acidification ofthe medium down to pH 7.0 and lower is similar to the pH-dependences observed for other hydrophobic ligands of serum albumin, varying in their charge and molecular features 13,14,22 Thus, a decrease in the affinity of hydrophobic binding sites of albumin on lowering pH may be a general mechanism underlying the deliver of hydrophobic substances to the membranes of cells in the areas of local tissue acidosis in both normal situations (e.g. pericellular space of liver or muscle under intensive loading) and pathological conditions (tumour, tissue ishemia, L 14,22 Deliganding HSA results in a rise in the absorbance and fluorescence of protein-bound dye and a short-wavelength shift ofthe dye fluorescence band (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…The discovered pH-induced changes in the N-form of albumin are not displayed in absorbance measurements (Figs. 5a, 5b) and were not detected by the methods of circular dichroism , 18 and 1H-NMR 17 jll as by use of other fluorescent probes monitoring N->B transition in serum albumin (ANS, bilirubin, warfarin, dansylaniide) 21, 22 A decrease in the HSA-NR affinity upon acidification ofthe medium down to pH 7.0 and lower is similar to the pH-dependences observed for other hydrophobic ligands of serum albumin, varying in their charge and molecular features 13,14,22 Thus, a decrease in the affinity of hydrophobic binding sites of albumin on lowering pH may be a general mechanism underlying the deliver of hydrophobic substances to the membranes of cells in the areas of local tissue acidosis in both normal situations (e.g. pericellular space of liver or muscle under intensive loading) and pathological conditions (tumour, tissue ishemia, L 14,22 Deliganding HSA results in a rise in the absorbance and fluorescence of protein-bound dye and a short-wavelength shift ofthe dye fluorescence band (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Albumin is not known to be synthesized in the testis, although in the rat testis a related protein, testibumin, is (Shaha et al, 1988). Interestingly, Melsert et al (1991) reported that albumin stimulates Leydig cell steroid production in a dose‐dependent manner in vitro when added to testicular fluid. While serum albumin is known to be distributed in the interstitial space in the testis (Christensen et al, 1985), it has been presumed to be there as a transudate from serum, and we are unaware of any suggestion of local synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Leydig cells in the testis interstitial compartment contribute 95–99% of circulatory testosterone ( Wu et al, 2017 ). Testosterone biosynthesis is catalyzed by SCARB1, STAR, CYP11A1, 3β-HSD, CYP17A1, and 17β-HSD3 ( Wang et al, 2011 ), which gets promoted when LH binds to LHCGR on its surface ( Melsert et al, 1991 ; Foster, 1996 ; Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gonadotrophs in the pituitary gland secrete luteinizing hormone (LH, LH-β subunit is encoded by Lhb ) ( Zhang et al, 2018 ). LH promotes Leydig cell development and androgen production by directly binding to luteinizing hormone/chorionic gonadotropin receptor (LHCGR) on its surface ( Melsert et al, 1991 ), leading to an increase in steroidogenic enzyme activity, particularly steroidogenic enzyme activities of rate-limiting STAR and CYP11A1, through cAMP-PKA signaling pathway ( Foster, 1996 ).…”
Section: Introductionmentioning
confidence: 99%